PROBLEMATIKA DAN STRATEGI DINAS PENDIDIKAN TERHADAP KETIDAKMERATAAN TENAGA PENDIDIK - Nita Rahmanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The teacher is an educator who becomes an example or role model for his students, a teacher is required to educate, teach, guide, direct, train, assess and evaluate his students, being a teacher may not be easy where a teacher must have extensive knowledge, good attitude, interesting skills. However, many schools have a shortage of teachers, especially in remote areas. This is one of the factors that causes inequality in teachers because they think that being a teacher pays a small salary and has to take care of a large number of children, so they think that it is not worth what they receive (salary). being one of the causes and to become a PNS/PPPK teacher is not easy. Moreover, many people think there are unseen people or people who have definitely passed because there are insiders who become very difficult competition to pass PNS/PPPK. Based on data from the National Civil Service Agency (BKN) annually issues CPNS formations, in 2021 there will be 1,002,616 CPNS formations for PPPK teachers. Meanwhile, the number of teachers in Indonesia, according to the Ministry of Education and Culture's Dapodik data, is 3,207,995. Nevertheless, as has been explained that education in Indonesia is not evenly distributed. There are also several solutions that the government has implemented, including SPGN (National Teacher Equalization System), additional teachers through regional contracts, mobilizing teachers, hiring honorary teachers through education and zoning. This research is focused on analyzing the problems of the education office regarding the inequality of educators/teachers. the approach used is a qualitative approach to the method of literature study.